2022
DOI: 10.3390/ijms231810448
|View full text |Cite
|
Sign up to set email alerts
|

First Discovery of Beta-Sitosterol as a Novel Antiviral Agent against White Spot Syndrome Virus

Abstract: The outbreak of white spot syndrome (WSS) is a looming challenge, due to dramatic losses to the crustacean aquaculture industry. However, at present, there are no prophylactic or therapeutic means to control this infectious viral disease. Here, we screened fifteen medicinal plants for their inhibitory activity on the white spot syndrome virus (WSSV), using red swamp crayfish (Procambarus clarkii) as a model species. The results showed that the crude extracts of Pinellia ternata (Thunb.) Breit. had the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…β-sitosterol (50 mg/kg), the main component of Pinellia ternata (Thunb.) Breit., was reported to inhibit ~95.79% of white spot syndrome virus (WSSV) in crayfish [ 113 ]. In addition, the stem bark, root, and leaf extracts of Erythrostemon yucatanensis (Greenm.)…”
Section: Resultsmentioning
confidence: 99%
“…β-sitosterol (50 mg/kg), the main component of Pinellia ternata (Thunb.) Breit., was reported to inhibit ~95.79% of white spot syndrome virus (WSSV) in crayfish [ 113 ]. In addition, the stem bark, root, and leaf extracts of Erythrostemon yucatanensis (Greenm.)…”
Section: Resultsmentioning
confidence: 99%
“…A recent in silico study suggested that β -sitosterol could suppress viral infection with SARS-CoV-2 through targeting the receptor-binding domain (RBD) of the spike glycoprotein [ 54 ]. Previous investigations have shown also that β -sitosterol exhibits antioxidant, anti-inflammatory, anticancer, and in vitro antiviral activity against white spot syndrome virus [ 51 , 52 , 53 , 54 ]. However, antiviral activities against IAVs, to the best of our knowledge, have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…One major compound, β -sitosterol, present in the LFOB, could block the immune responses mediated by RIG-I signaling and deleterious IFN production that could help to reduce the viral load [ 31 ]. Furthermore, it has also been reported that it interferes with viral gene expression and inhibits viral replication by interfering with viral immune signaling, hijacking pathways [ 32 ]. As of now, there are no reports available on β -sitosterol, stigmasterol and campesterol targeting DENV proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The oven temperature programmed with linear mode went from 60 °C to 280 °C at a 3 °C/min ramp; using nitrogen (1.0 mL/min flow rate), for the injector and detector, temperatures were fixed at 290 °C and 300 °C, respectively. The injection volume was 1.0 μL of 1% solution, and the split ratio was set at 1:50 [ 30 , 31 , 32 ]. The ITQ 1100 interfaced Trace Ultra Gas Chromatography-Mass Spectroscopy (GC-MS) (Thermo Scientific, Waltham, MA, USA) was employed for qualitative analysis with the column mentioned above and GC oven temperature program using helium as a carrier gas at 1.0 mL/min.…”
Section: Methodsmentioning
confidence: 99%